MENINGKATKAN KEMAMPUAN MEMBACA DAN MENULIS AKSARA JAWA MELALUI METODE DRILL - Suwarsi - (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2015)
Class Action Research (CAR) to improve the ability to read and write Java script through the drill method in grade V SDN Ngepeh 3 Loceret Subdistrict In Nganjuk Regency Lesson 2014/2015. Research subjects consisted of 20 people grade V SDN Ngepeh 3, Loceret, Nganjuk. Research Action Class consists of 4 stages, namely; planning, implementation measures, observation and reflection, with a view to comparing the value of an action before and after the action. Types of methods used in the collection of data disesuailkan with the nature of research that is done. Data collected through observations, tests, field notes, documentation, and special notes from special need students. Results of analysis showed that the use of the drill method, a total of 13 students who completed and only 7 students who hadn't (cycle 1). On cycle II all students of 20 students have achieved 100% learning completion with details of the average value of a home study class at 60.50; on cycle 1 increased by 77.50; While on cycle II the average of value score reached is 85.50. KEYWORD: reading skill’s, writing aksara jawa skill’s, and drill method’s